IMPLEMENTASI NILAI-NILAI PENDIDIKAN KEAGAMAAN PADA MASYARAKAT DESA SAMANGKI KECAMATAN SIMBANG KABUPATEN MAROS - Darwana; Ismail; Palili, sampara (An-Nahdlah: Jurnal Pendidikan Islam, 2024)
Facing advances in various fields of science and technology, often brings changes in the lives of society in general. Thought patterns and behavioral patterns also experience changes and existing habits can be replaced by new habits which may result in people neglecting their main duties. So, to avoid this, it is necessary to implement the values ​​of religious education in people's lives. The aim of this research is to examine and implement the values ​​of religious education in the Samangki Village community. This type of researcher is qualitative with a phenomenological approach. The results of the research show that: 1) the description of the implementation of religious education values ​​in the Samangki village community includes four main aspects, namely implementation: (a) religious values, (b) friendship values, (c) politeness values, and (d) mutual respect values ; 2) Implementation of religious education values ​​in the Samangki village community through two stages, namely, (a) through religious activities, and (b) through daily behavior; 3) the results of the implementation of religious education values ​​show that the Samangki village community is very enthusiastic and actively involved in religious activities.